PERBEDAAN KUAT TEKAN SEGMEN KOLOM MODULER BETON PECAHAN GENTENG DENGAN SEGMEN KOLOM MODULER BETON PECAHAN BATA MERAH PADA RUMAH TUMBUH - Chundakus Habsya (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2008)
The objectives of this research were: (1) is there any difference between compressive strength the moduler column segment of tile fraction concrete with the moduler column segment of red brick fraction concrete (2) is there any difference between specific gravity the moduler column segment of tile fraction concrete with the moduler column segment of red brick fraction concrete (3) percentage of clay fulfilling of optimal quality moduler column segment. This research used the quantitative method experiment by compression test. Population used by 33 moduler column segment 150 mm x 150 mm x 300 mm with variation of the percentage of red brick fraction and tile fraction replacement 0%, 20%, 40%, 65%, 80%, 100%. Data Technique analyzes used was the equations mark with lines the regression with the level significance 1%. Conclusion from this research is: (1) There was difference between compressive strength the moduler column segment of tile fraction concrete with the moduler column segment of red brick fraction concrete. On the moduler column segment of tile fraction concrete with percentage of 40%, 60% compressive strength equal to 15.81 Mpa and 15.04 Mpa fulfill the structure standard and the moduler column segment of red brick fraction concrete with percentage of 40%, 60% compressive strength equal to 8.92 Mpa, and 6.56 Mpa not fulfill the structure standard (2) There was difference between specific gravity the moduler column segment of tile fraction concrete with the moduler column segment of red brick fraction concrete at variation of percentage of 40% and 100%. (3) Optimal quality of moduler column segment of tile fraction concrete with percentage of 40%, compressive strength 15.81 Mpa, specific gravity 2217.05 kg/ m³.